1997
DOI: 10.1063/1.475031
|View full text |Cite
|
Sign up to set email alerts
|

A reanalysis of the k3Π state of CO

Abstract: Articles you may be interested inA critical re-assignment of the Rydberg states of iodomethane based on new polarization data J. Chem. Phys. 138, 134308 (2013); 10.1063/1.4798972[1 + 1] photodissociation of CS 2 + ( X ̃ 2 Π g ) via the vibrationally mediated B ̃ 2 Σ u + state: Multichannels exhibiting and mode specific dynamicsThe k 3 ⌸ state of the CO molecule is investigated in the region between 91 000 and 97 000 cm Ϫ1 via 1ϩ1 resonance enhanced multiphoton ionization spectroscopy on CO molecules prepared i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 20 publications
3
27
0
Order By: Relevance
“…Mazeau et al 13 also identified another feature at 94 245± 81 cm −1 ͑11.685± 0.01 eV-their feature b͒, under different electron energy and scattering angles, which can now be associated with the k 3 ⌸ ͑v =5͒ state. 16,20 The difference between their term value and the location of the k -X ͑5-0͒ observed in this study at Ϸ94 437 cm −1 lies somewhat outside of the estimated experimental error by Mazeau et al Table IV. The other study requires a more detailed consideration as it appears to be inconsistent with our study.…”
Section: Results and Analysismentioning
confidence: 48%
See 4 more Smart Citations
“…Mazeau et al 13 also identified another feature at 94 245± 81 cm −1 ͑11.685± 0.01 eV-their feature b͒, under different electron energy and scattering angles, which can now be associated with the k 3 ⌸ ͑v =5͒ state. 16,20 The difference between their term value and the location of the k -X ͑5-0͒ observed in this study at Ϸ94 437 cm −1 lies somewhat outside of the estimated experimental error by Mazeau et al Table IV. The other study requires a more detailed consideration as it appears to be inconsistent with our study.…”
Section: Results and Analysismentioning
confidence: 48%
“…As previously mentioned the band shown in Fig. 2 20 As described in the Introduction, Berden et al 20 performed a 1 + 1 REMPI study on metastable a 3 ⌸ CO molecules. Three lines corresponding to 1 + 1 REMPI via the k 3 ⌸ ͑v =5͒ state of CO molecules, initially prepared in the a 3 ⌸ ͑v =1, J =1, ⍀ =1, f parity͒ state, were identified and assigned.…”
Section: Results and Analysismentioning
confidence: 94%
See 3 more Smart Citations